Pathways for learning : education and training from 16 to 19 - (:unkn) unknown (My University, 1989)
"The years immediately following the end of full-time post- compulsory education are among the most complex and critical in any education system. They are complex because they are affected by a wide range of factors: the nature and output of compulsory education, the diverse needs and aspirations of young people, the changing demands of the labour market, the problems of youth unemployment, the influence of higher and continuing education. The post-compulsory stage is a critical one for the individual since it involves important educational, career and even life choices, and for the system because it forms a crucial linkage between education and the economy. Member countries have very different institutional arrangements at this stage and are, therefore, confronted with problems specifically related to their own distinctive settings. All countries, however, share a strong interest in and support for qualitative changes, considered essential in coping with the common issues and dilemmas they currently confront at this level. Thus, the aim of the present report is to clarify current curriculum issues in post-compulsory (approximately 16 to 19) education focusing primarily on the structure and content of courses and the qualifications to which they lead." (author's abtract) ((en)) Der Bericht versucht gegenwärtig bestehende Curriculumprobleme von Bildung, Schule und Ausbildung nach Erfüllung der Schulpflicht, also für 16-19 jährige Jugendliche, zu klären, wobei er sich auf Struktur, Ausbildungsinhalte und Qualifikationsvermittlung konzentriert. Der Bericht stützt sich auf OECD-Länderberichte für 11 Mitgliedstaaten. (IAB)
Lernpfade. Bildung und Weiterbildung im Alter von 16 bis 19 Jahren
Keywords: S 1.1 Allgemeinbildende Schule; L 1 Curricula & Lehrpläne; S 2.2 Ordnungen & Ordnungsverfahren; G 2.2.1 Technologisierung; S 3 Institutionen; G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; Jugendlicher; Berufsausbildung; Internationaler Vergleich; Betriebliche Berufsausbildung; Berufsbildendes Schulwesen; Sekundarbereich; Allgemeinbildendes Schulwesen; Curriculum; Ausbildungsinhalt; Bildungsinhalt; Technischer Wandel; Lernort; Qualifikationsvermittlung; Quantitative Angaben